Jews and their Biblical Kin in Conflict: Fabricating Internal Dissent in Medieval Anti-Jewish Dialogues - Kitsos, Michail (Studies in Christian-Jewish Relations, 2024)
In the anonymously written Adversus Iudaeos dialogues, which describe staged theological discussions between Christians and Jews and are replete with performative elements to enhance the dramatization of such encounters, the image of the Jew who attacks Christianity is a recurrent trope. Despite the Jew’s central role in these texts, the reasons for his diachronic employment require further scrutiny. This article addresses this gap by examining the function of the Jew as a foil to his Christian interlocutor. In particular, this article scrutinizes discussions on the virgin birth of Jesus, the Christological title Son of God, and the number of Gods involved in the creation from three anonymous early medieval anti-Jewish dialogues originating from the broader Byzantine Mediterranean—The Dialogue of Timothy and Aquila, The Dialogue of Papiscos and Philo, Jews, with a Monk, and the Altercation of Simon and Theophilus. It argues that the Christian authors of anti-Jewish dialogues deployed the Jew as a foil to his Christian interlocutor and to biblical Israelite authors with whom they portray him to share a genealogical affinity to claim religious legitimacy of Christian teachings and to reject the Jews’ portrayed claims of the legitimacy of his own beliefs. This article shows that foiling the Jew was an essential rhetorical tool in Christian anti-Jewish polemics to legitimize Christianity, and it can inform the similar use of other characters in dialogue texts that belong to the polemical genre from different theological contexts.* * Translations are all mine unless otherwise stated. For an English translation of biblical verses from the Septuagint (LXX), that is, the Greek translation of the Hebrew Bible, I used Albert Pietersma and Benjamin G. Wright, eds., A New English Translation of the Septuaginta: And the Other Greek Translations Traditionally Included under that Title (Oxford: Oxford University Press, 2007). For an English translation of biblical verses from the Hebrew Bible (MT), I used the JPS Hebrew-English Tanakh: The Traditional Hebrew Text and the New JPS Translation (Philadelphia: The Jewish Publication Society, 1999) [On the Greek translation of the Septuagint see, Jennifer M. Dines, The Septuagint, ed. Michael A. Knibb (London: T&T Clark, 2004); and also, Emanuel Tov, “The Septuagint,” in Mikra: Text, Translation, Reading and Interpretation of the Hebrew Bible in Ancient Judaism and Early Christianity, ed. Martin Jan Mulder and Harry Sysling (Peabody, MA: Hendrickson Publishers, 2004), 161-188. For an English translation of New Testament passages, I used the New King James Version.